(untitled) (Journal of Education and Development, 2024)
Young children’s self-regulation (executive function; approaches to learning) and early language functions have been shown to independently predict children’s achievement in school, particularly reading and mathematics. Controlling for SES, gender and age at kindergarten entry, hierarchical multiple regression was used to test the hypothesis that children’s executive functions, approaches to learning, and early language functions at the beginning of kindergarten would predict third-grade reading, mathematics, and science achievement. Third-grade is a benchmark year as it usually marks the beginning of standardized testing and plays a pivotal role in determining children’s academic trajectories. Data from the Early Childhood Longitudinal Study Kindergarten Class of 2010-2011 (ECLS-K: 2011) were used to test the hypotheses. The hypothesized models suggest that executive function, approaches to learning, and language functions measured at the beginning of kindergarten are predictive of third-grade academic achievement. While the factors were individually predictive, the regression model was the strongest when it included the factors collectively. Implications for both policy and practice are noted.